Bareback Sex in the Age of Preventative Medication: Rethinking the 'Harms' of HIV Transmission. (December 2020) - Ashford, Chris; Morris, Max; Powell, Alex
The experiences of people living with HIV have been transformed over recent years. Advances in medical science have made the virus a manageable chronic condition, while eliminating the risk of onward transmission for those with access to treatment, something referred to as TasP (treatment as prevention) or U=U (undetectable equals untransmissible). More recently, the availability of PrEP (pre-exposure prophylaxis), alongside PEP (post-exposure prophylaxis), through the NHS has created the conditions for condomless sexual encounters to take place without the fear of HIV transmission associated with previous decades. Despite this, the criminal law has continued to frame HIV in terms of personal responsibility and bodily autonomy within the dominant narratives of danger, disease, and out-dated science. Doctrinal law has failed to keep pace with social and scientific change. Therefore, in this article, we provide a re-examination of the criminal issues relating to HIV transmission within this new landscape, arguing that it necessitates a shift in attitude, policy and doctrine. We specifically argue that HIV transmission does not meet the appropriate harm threshold to constitute GBH and that if criminal law is ultimately about preventing or regulating harm, the ongoing criminalisation of HIV transmission is counter to that aim.